2019
DOI: 10.1039/c8cp06656f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent reorganization triggers photo-induced solvated electron generation in phenol

Abstract: Charge-transfer states with large electron–hole separation, correlating to the formation of solvated electrons, are found below the maximum of the absorbing ππ* band of solvated phenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…For the QM/EFP calculations, the QM region was selected to be phenol plus the ve water molecules closest to any atom within phenol. Although fewer water molecules have been employed for other calculations of phenol in aqueous solution, 34,43 we used ve because we found this was enough to ensure that all the water molecules that are hydrogen-bonded to phenol (donor-acceptor distance < 3Å, donor-H-acceptor bond angle 180 AE 20 ) were included in the QM region. The EFP region was selected to be all other water molecules within 10Å of any atom in the phenol molecule (250-300 water molecules).…”
Section: Computationalmentioning
confidence: 99%
“…For the QM/EFP calculations, the QM region was selected to be phenol plus the ve water molecules closest to any atom within phenol. Although fewer water molecules have been employed for other calculations of phenol in aqueous solution, 34,43 we used ve because we found this was enough to ensure that all the water molecules that are hydrogen-bonded to phenol (donor-acceptor distance < 3Å, donor-H-acceptor bond angle 180 AE 20 ) were included in the QM region. The EFP region was selected to be all other water molecules within 10Å of any atom in the phenol molecule (250-300 water molecules).…”
Section: Computationalmentioning
confidence: 99%
“…Gonzalez and co-workers carried out computational studies of the related heteroatomic molecule phenol microsolvated by 15 water molecules, and they described the presence of a charge-transfer (CT) state: an electron promoted from an π orbital on phenol to a σ*-type orbital located in the solvent. The calculations returned very low oscillator strengths for the CT state and showed that the CT minimum is lower in energy than that of the optically bright 1 ππ* state . We propose that the aforementioned theoretical discussion of CTTS or CT states in related heteroaromatics molecules is another way of describing, or even synonymous with, a tightly bound cation–electron contact ion-pair, , e.g., [Ind + :e – ], where the surfaces of the cation and electron are in direct contact with no solvent molecules in between.…”
Section: Discussionmentioning
confidence: 88%
“…The calculations returned very low oscillator strengths for the CT state and showed that the CT minimum is lower in energy than that of the optically bright 1 ππ* state. 76 We propose that the aforementioned theoretical discussion of CTTS or CT states in related heteroaromatics molecules is another way of describing, or even synonymous with, a tightly bound cation–electron contact ion-pair, 63 , 77 e.g., [Ind + :e – ], where the surfaces of the cation and electron are in direct contact with no solvent molecules in between.…”
Section: Discussionmentioning
confidence: 99%
“…Excitation energies are shown in Table . There are many studies of electronic excitations of phenol. An experimental adsorption wavelength for the lowest singlet (π → π*) is 267 nm (4.644 eV) . An overlay of the ground and excited state optimized structures of phenol is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%